Transboundary landscapes and rural livelihoods: a case study from the northern Kwazulu-Natal and Mozambique border - Mahlaba, Simlindile (Department of Environmental and Geographical Science, 2021)
Transboundary landscapes were introduced to southern Africa through colonialism and persist in the present day. These transboundary landscapes are constructed through political boundaries separating states as well as through the linkage of nature reserves and game parks located in adjacent countries. These landscapes have caused shifts in the livelihoods of the rural communities existing near them. This is the case for the Mbangweni rural area in northern KwaZulu-Natal in South Africa. This rural area, located in a transboundary landscape formed by the national border that separates Mozambique and South Africa, sits in between Ndumo Game Reserve and Tembe Elephant Park. The proposed linkage of these two nature reserves to each other and to the Maputo Special Reserve in Mozambique seeks to create a transboundary landscape that has negative consequences for the livelihoods of the Mbangweni community. Through the analysis of this rural community and the nature reserves on either side of it, this research sought to enhance understanding about how rural communities interact with transboundary landscapes, as well as the perceptions held by these rural communities and other actors (especially within the conservation sector) about how these landscapes influence rural livelihoods as well as the consequences of these landscapes on rural livelihoods. The study sought to also understand the level of institutional fit and interplay that exists between the institutions that govern over this landscape as well as between the institutions and the lived realities of the Mbangweni community by documenting the historical and current transboundary livelihood practices of the people of Mbangweni, determining the manner in which government actors and conservation authorities perceive and conceive of the transboundary landscape, determining whether or not (and to what extent) local and government perceptions about the transboundary landscape in Mbangweni are similar, and if not, how that affects livelihood activities on the ground and visually mapping out the different perceptions of the landscape held by the Mbangweni community and associated governing institutions. Qualitative data collection methods were used. These included 10 oral history interviews, 2 focus groups and 3 key informant interviews. The findings of this study reveal that the initial establishment of the transboundary landscape in this region led to the separation of the population of the Maputaland. The communities in northern KwaZulu-Natal and those in southern Mozambique once lived as a single population group. The national border separating South Africa from Mozambique was introduced and forced some of the population to settle on one side of the border and the rest on the other side. Although initially very rigid, the border's laws now allow for the informal movement of people and trade of goods between the southern Mozambique and northern KwaZulu-Natal areas. The study, therefore, found that the border's porous nature had a positive impact on the livelihoods of the people of Mbangweni. The findings also revealed that in addition to the national border, other institutions and entities were considered important for the livelihoods of the community. These institutions and entities include the traditional authority, the local municipality and the nature reserves adjacent to the Mbangweni community. These key role players each contributed to and impacted the rural livelihoods with the traditional authority having the biggest influence and most positive impact, the local municipality having the smallest influence and not much of an impact and the nature reserves having relatively minimal influence on the daily conduction of livelihoods but the most negative impact on how these livelihoods are conducted and sustained. Furthermore, the study showed that the key role players hold differing perceptions of the landscape and that these perceptions also differ from those held by the Mbangweni community. The study showed that the disconnect in perceptions of the landscapes results in isolated and fragmented land use by the entities and institutions occupying the same space. Conflict then arises due to the entities understanding and viewing the landscape as a space for different priorities. The nature reserves and their governing institution prioritise natural resource conservation and the Mbangweni community and the traditional authority, as its governing institution, prioritise their livelihoods and access to natural resources. These differing perceptions of the landscape perpetuate the institutional misfit and lack of interplay between the entities and governing institutions. The study found that even with different understandings of the landscape they occupy, each entity and relevant governing institution have the potential to facilitate institutional bricolage which would require adjustments of and changes to their mandates and goals to accommodate the mandates and goals of other institutions, other entities as well as the lived realities of the Mbangweni community. By fostering this bricolage, a transboundary landscape that adequately serves the needs and purposes of all its entities, whilst minimising opportunities for conflict between them, would be created.